2021
DOI: 10.3390/cancers13051102
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Cancer Cell Responses Driving Radioresistance of Hypoxic Tumors: Approaches to Targeting and Radiosensitizing

Abstract: Within aggressive malignancies, there usually are the “hypoxic zones”—poorly vascularized regions where tumor cells undergo oxygen deficiency through inadequate blood supply. Besides, hypoxia may arise in tumors as a result of antiangiogenic therapy or transarterial embolization. Adapting to hypoxia, tumor cells acquire a hypoxia-resistant phenotype with the characteristic alterations in signaling, gene expression and metabolism. Both the lack of oxygen by itself and the hypoxia-responsive phenotypic modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 342 publications
0
52
0
Order By: Relevance
“…Some of them were able to improve the local control of the tumor but appeared too difficult to set up in a clinical routine ( 131 ). More recently, several pre-clinical studies established a rationale for combining radiotherapy with HIF-1 inhibitor ( 132 , 133 ), leading, for example, to a phase I clinical trial using PX-478 in advanced solid tumors (NCT00522652).…”
Section: Reoxygenation: Radiation-induced Hypoxia-like Signaling Restricts Reoxygenation Effectmentioning
confidence: 99%
“…Some of them were able to improve the local control of the tumor but appeared too difficult to set up in a clinical routine ( 131 ). More recently, several pre-clinical studies established a rationale for combining radiotherapy with HIF-1 inhibitor ( 132 , 133 ), leading, for example, to a phase I clinical trial using PX-478 in advanced solid tumors (NCT00522652).…”
Section: Reoxygenation: Radiation-induced Hypoxia-like Signaling Restricts Reoxygenation Effectmentioning
confidence: 99%
“…As a fibric acid derivative displacing oxygen from hemoglobin to hypoxic tissue ultimately leading to an increase of oxygen delivery, efaproxiral exhibited promising results in phase I/II but failed in the later phase of clinical development, especially as a radiosensitiser and hypoxic target therapies [ 374 , 375 , 376 ]. Several additional clinical trials are ongoing with novel radiosensitisers [ 377 , 378 ], and modified radiotherapy protocols according to the hypoxic region to enhance immune cytogenic anti-cancer effect [ 379 , 380 ].…”
Section: Hypoxia-related Treatments and Research Developmentmentioning
confidence: 99%
“…For this reason, the dynamics of abnormal vessel growth that arise in tumor tissue due to angiogenesis [ 61 ] are not taken into account. Furthermore, it has been shown that radiation therapy can cause hypoxia [ 62 ] or upregulate HIF-1 expression [ 63 ], which in turn leads to a development and selection of more resistant cells [ 64 , 65 ]. Moreover, the biological effects induced by other pharmaceuticals, e.g., the effect of androgen-deprivation therapy with bicalutamide in selecting more resistant cells to the treatment [ 66 ], are not considered at this stage.…”
Section: Discussionmentioning
confidence: 99%